Amakudari : the hidden fabric of Japan's economy - Colignon, Richard A., 1951- (Cornell University Press, 2003)
"The widespread migration of civil servants to high-profile positions in the private and public sectors is known in Japan as amakudari, or "descent from heaven." Recent media stories associate the practice with corruption as the former officials seek government favors for their new employers. In their timely book, Richard A. Colignon and Chikako Usui offer the first systematic exploration of this influential yet poorly understood Japanese institution." "Colignon and Usui analyze amakudari as a ministry-level phenomenon that is consciously constructed and reproduced with intricate networks in many political and corporate spheres. Drawing on five decades of qualitative and quantitative data delineating the post-retirement careers of leading bureaucrats, they examine changes in traditional job patterns. Although not as strong a force as in the 1960s and 1970s, amakudari, in their view, remains a critical feature of Japanese society and heavily shapes the relationship between government and business." "The authors warn that despite the Japanese media criticism of amakudari, it comprises a power structure resistant to radical change. Most important, their book demonstrates that a gradual weakening of this practice may not lead to a more democratic, meritocratic society."--Jacket